Pola Asuh Otoriter Yang di Terapkan Orang Tua Kepada Anak Usia Dini Saat Pembelajaran Daring - Siti Mutmainah; Nila Ma’rifatus Sholihah (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This research is motivated by the many outpouring of the parents' hearts in how to educate their children to have a personality that is characterized and independent and responsible when they grow up, especially now in online learning situations, parents are confused about how to apply the right learning parenting pattern in order to get results. according to expectations. This study aims to determine the effectiveness of parenting on the formation of children's character from an early age. This research was conducted using a descriptive method with a quantitative approach which was carried out by collecting data using a questionnaire. The research subjects were PAUD Guardians and RA Darul Muqomah Jember. The results showed that around 70% of respondents thought that authoritarian parenting is important in building character from an early age.